A Molfar of a poetic word - Мелешко, Віра Анатоліївна; Степаненко, Микола Іванович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
A Molfar of a poetic word. a review of the publication: Dziuba A. Molfar’s travels: a collection of poems. Kyiv: Autograph, 2017. 328 p